2003
DOI: 10.1081/pfc-120019901
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Low Doses of Endosulfan and Chlorpyrifos Modifies Endogenous Antioxidants in Tissues of Rats

Abstract: Two experiments were conducted in male SD rats (225-250 g) to determine changes in the activities of endogenous antioxidants superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX) and concentrations of glutathione (GSH) in tissues after exposure to low doses of endosulfan and chlorpyrifos using a whole body exposure technique. In both experiments, 6 rats/group were exposed 3 hr/day, 5 days/week for 30 days to: 0 (control), 5, 10, 20, 40 and 60% of LD50 of either pesticide in 50% ethanol; actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(68 citation statements)
references
References 29 publications
5
63
0
Order By: Relevance
“…These results are in agreement with who reported enhancement of MDA production, decrease in reduced glutathione content, glutathione-S-transferase and catalase activities in rat tissues that treated with CPF [45]. Also, other previous studies have been reported accumulation of lipid peroxides in rat liver after exposure to acute dose of cholrpyrifos and kidney while, repeated doses of CPF increased LPO levels as well as decreased antioxidant enzymes in rat liver and lung [46][47][48][49].…”
Section: Journal Of Medical Toxicology and Clinical Forensic Medicinesupporting
confidence: 82%
“…These results are in agreement with who reported enhancement of MDA production, decrease in reduced glutathione content, glutathione-S-transferase and catalase activities in rat tissues that treated with CPF [45]. Also, other previous studies have been reported accumulation of lipid peroxides in rat liver after exposure to acute dose of cholrpyrifos and kidney while, repeated doses of CPF increased LPO levels as well as decreased antioxidant enzymes in rat liver and lung [46][47][48][49].…”
Section: Journal Of Medical Toxicology and Clinical Forensic Medicinesupporting
confidence: 82%
“…The modulation of SOD activity by pesticides is reported to be variable with low doses of some pesticides not altering, but higher doses increasing activity in the liver and other tissues. [11,13,19,20] More recently, Gao et al [21,22] have shown that feeding of flavonoid rutin at 2.25 g/kg body weight to mice or rats did not alter hepatic Zn, Cu SOD activity, but significantly decreased catalase activity along with an increase in total antioxidant status in the liver. The present data suggest that the increase in liver SOD activity after long-term feeding of FM with and without PM exposure may be a result of increased intracellular free radical oxygen accumulation that may have been generated by auto-oxidation and/or metabolism of FM by the drug metabolizing Phase I enzyme cytochrome 450 1A1.…”
Section: Discussionmentioning
confidence: 99%
“…45 Chlorpyrifos has been found to modify endogenous antioxidants in rats, possibly leading to the development of oxidative stress. 46 A case-control study reported increased risk of non-Hodgkin's lymphoma 47 and glioma 48 among male farmers exposed to chlorpyrifos in the United States. In a previous analysis of cancer among chlorpyrifos users in the Agricultural Health Study cohort, we reported an increased risk of rectal cancer consistent with our current findings, as well as excesses for cancers of the lung and brain.…”
Section: Discussionmentioning
confidence: 99%